Crystal structure of the cold-adapted haloalkane dehalogenase DpcA from Psychrobacter cryohalolentis K5 - Tratsiak, Katsiaryna; Prudnikova, Tatyana; Drienovska, Ivana; Damborsky, Jiri; Brynda, Jiri; Pachl, Petr; Kuty, Michal; Chaloupkova, Radka; Rezacova, Pavlina; Kuta Smatanova, Ivana (Acta crystallographica. Section F, Structural biology communications, 2019)
Haloalkane dehalogenases (HLDs) convert halogenated aliphatic pollutants to less toxic compounds by a hydrolytic mechanism. Owing to their broad substrate specificity and high enantioselectivity, haloalkane dehalogenases can function as biosensors to detect toxic compounds in the environment or can be used for the production of optically pure compounds. Here, the structural analysis of the haloalkane dehalogenase DpcA isolated from the psychrophilic bacterium Psychrobacter cryohalolentis K5 is presented at the atomic resolution of 1.05 Å. This enzyme exhibits a low temperature optimum, making it attractive for environmental applications such as biosensing at the subsurface environment, where the temperature typically does not exceed 25°C. The structure revealed that DpcA possesses the shortest access tunnel and one of the most widely open main tunnels among structural homologs of the HLD-I subfamily. Comparative analysis revealed major differences in the region of the α4 helix of the cap domain, which is one of the key determinants of the anatomy of the tunnels. The crystal structure of DpcA will contribute to better understanding of the structure-function relationships of cold-adapted enzymes.
Keywords: Hydrocarbons, Halogenated; Protein Binding; exprese genu; Gene Expression; Recombinant Fusion Proteins; Psychrobacter cryohalolentis; krystalografie rentgenová; konformace proteinů, beta-řetězec; vazebná místa; interakční proteinové domény a motivy; Bacterial Proteins; Thermodynamics; Cloning, Molecular; Protein Conformation, beta-Strand; klonování DNA; Psychrobacter; halogenované uhlovodíky; Amino Acid Sequence; Genetic Vectors; Hydrolases; Escherichia coli; konformace proteinů, alfa-helix; Molecular Docking Simulation; rekombinantní fúzní proteiny; hydrolasy; haloalkane dehalogenase; strukturní homologie proteinů; Crystallography, X-Ray; Protein Interaction Domains and Motifs; simulace molekulového dockingu; termodynamika; vazba proteinů; Binding Sites; substrátová specifita; Substrate Specificity; Protein Conformation, alpha-Helical; X-ray diffraction; bakteriální proteiny; psychrophiles; sekvence aminokyselin; genetické vektory; structural analysis; Structural Homology, Protein; α/β-hydrolase; nízká teplota; Cold Temperature